PENGEMBANGAN UMKM MELALUI LITERASI DIGITAL PADA DESA PARENGAN KECAMATAN MADURAN - Muhammad Iqbal M; Sawabi; Didik Puji Wahyono; Ardiansyah AH; Sukahar; Sutikno (CV. ALIM'SPUBLISHING, 2023)
Parengan Village is one of the leading villages located in Maduran District, Lamongan Regency. Parengan village has a lot of good potential. There are 16 MSMEs that are the source of life for the people of Parengan Village with various types of businesses consisting of woven crafts, woven sarongs, handicrafts, cosmetic businesses, food businesses, livestock businesses, agriculture to service providers. This service involved 16 MSME partners who were in Parengan Village. The problem faced by MSME partners in Parengan Village is a lack of understanding of digital literacy, so that in running their business most of them still use conventional methods. To help solve the problems faced by MSME partners, socialization was carried out regarding digital literacy and assistance in implementing digital MSMEs. The stages carried out in this service consist of 4 stages, starting from the coordination stage, the socialization stage, the mentoring stage and the evaluation stage. The results of the socialization activities that have been carried out show that knowledge and insight regarding digital literacy has increased, this is supported by a desire to learn from MSME partners in digitizing their businesses. Then from the mentoring activities that have been carried out, it shows that MSME partners have started to be able to implement their business promotions through social media such as Instagram, Facebook and WA Business as well as make sales through e-commerce sites such as Shopee, Tokopedia or Lazada